A Pseudo-Parabolic Type Equation with Nonlinear Sources (Communications in Mathematical Research, 2021)
This paper is concerned with the existence and uniqueness of nonnegativeclassical solutions to the initial-boundary value problems for the pseudo-parabolicequation with strongly nonlinear sources. Furthermore, we discuss the asymptoticbehavior of solutions as the viscosity coefficient $k$ tends to zero.